Deciphering the salinity adaptation mechanism in Penicilliopsis clavariiformis AP, a rare salt tolerant fungus from mangrove. (11th December 2015) - Kashyap, Prem Lal; Rai, Anuradha; Singh, Ruchi; Chakdar, Hillol; Kumar, Sudheer; Srivastava, Alok Kumar
Abstract : Penicilliopsis clavariiformis AP, a rare salt tolerant fungus reported for the first time from India was identified through polyphasic taxonomy. Scanning electron microscopy showed that the fungus has unique features such as biverticillate penicilli bearing masses of oval to ellipsoidal conidia. The fungus has been characterized for salt tolerance and to understand the relevance of central carbon metabolism in salt stress adaptation. It showed optimal growth at 24 °C and able to tolerate up to 10% (w/v) NaCl. To understand the mechanism of adaptation to high salinity, activities of the key enzymes regulating glycolysis, pentose phosphate pathway, and tricarboxylic acid cycle were investigated under normal (0% NaCl) and saline stress environment (10% NaCl). The results revealed a re‐routing of carbon metabolism away from glycolysis to the pentose phosphate pathway (PPP), served as a cellular stress‐resistance mechanism in fungi under saline environment. The detection and significant expression of fungus genes ( Hsp98, Hsp60, HTB, and RHO ) under saline stress suggest that these halotolerance conferring genes from the fungus could have a role in fungus protection and adaptation under saline environment. Overall, the present findings indicate that the rearrangement of the metabolic fluxes distribution and stress related genes play an important role in cell survival and adaptation under saline environment.